Uniportal Subcostal Video-Assisted Thoracoscopic Surgery: A Feasible Approach for a Challenging Middle Lobectomy in an Obese Patient - Samer Al Sawalhi; Deping Zhao; Haomin Cai; Yuxing Jin (Case Reports in Pulmonology)
Subcostal access is a novel approach for anatomical lung resection. To perform surgery via this access, specially designed long instruments are required. Subcostal access provides excellent visualization of the mediastinum and anterior lung hilum. We exhibit here a subcostal middle lobectomy with systematic en-block mediastinal lymphadenectomy in an obese 52-year-old male patient with body mass index (BMI=37.7) performed via this single incision. The operation was completed efficiently within 30 minutes with negligible postoperative pain.